Gamma interferon levels and antibody production induced by two PvMSP-1 recombinant polypeptides are associated with protective immunity against P. vivax in Aotus monkeys (2005)
Effector mechanisms responsible for providing protective immunity against Plasmodium vivax (Pv) infection were examined in Aotus monkeys vaccinated with two Pv Merozoite Surface Protein-1 (PvMSP-1) recombinant polypeptides that had previously been shown to protect vaccines against parasite challenge. Vaccine efficacy was reproducible in this trial, showing that one out of the five monkeys immunised with the recombinant protein mixture was partially protected while three others controlled parasitaemia. Antibodies reactive to the parasite's native proteins, the recombinant polypeptides and peptides spanning both recombinant fragments were detected in most vaccinees. Despite substantial Peripheral Blood Mononuclear Cell (PBMC) antigen-specific cellular proliferation not being detected, high rPvMSP-120 specific gamma interferon (IFN-?) production was found in the three animals that controlled parasitaemia. Altogether the results suggest that antibody titres and antigen-specific IFN-? production mediate protective immunity against P. vivax.